PERSEPSI GURU PENDIDIKAN AGAMA ISLAM TERHADAP KEGIATAN SPIRITUAL DAN SOSIAL SISWA KELAS VIII DI SEKOLAH MENEGAH PERTAMA (SMP) NEGERI 8 MUARO JAMBI - Olivia Saputri, Nadya; Fahri, Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine and analyze the perceptions of Islamic Religious Education (PAI) teachers regarding the spiritual and social activities of eighth-grade students at SMP Negeri 8 Muaro Jambi. The study is grounded in the important role of PAI teachers in shaping students’ character, particularly in spiritual aspects such as religious discipline, honesty, and gratitude, as well as social aspects including cooperation, empathy, and responsibility. A descriptive qualitative approach was employed. Data were collected through observation, interviews, and documentation involving PAI teachers and eighth-grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing, and the validity of the findings was ensured using triangulation. The findings indicate that teachers perceive students’ spiritual and social activities as generally positive. Students demonstrate habits such as praying before lessons, participating in religious programs, and showing care and cooperation in social activities. Nevertheless, several challenges remain, particularly limited discipline among some students and insufficient depth of religious understanding. Overall, the spiritual and social development of students has progressed positively due to continuous guidance and exemplary practices provided by PAI teachers at the school.